Costs of surgical treatment of urinary incontinence in women - Rechberger, Tomasz; Postawski, Krzysztof; Charachajczuk, Klaudia (Menopause Review/Przegląd Menopauzalny, 2009)
Objective: To estimate costs for surgical treatment of urinary incontinence surgery in women by applying retropubic Burch colposuspension or modern sling procedures. Material and methods: A total of 52 procedures were randomly chosen from a cohort of 1329 stress urinary incontinence (SUI) operations performed during 1999–2007 in the 2nd Department of Gynaecology, Medical University of Lublin. There were 10 Burch open and 8 laparoscopic version of colposuspension, 10 TVT, 10 IVS-02, 10 IVS-04 and four TVT-O slings. Mean costs in Polish zlotys for each procedure were calculated according to: time of procedure, mode of anaesthesia used and sum of money spent for surgical supplies including disposable kits and surgical procedure kits such as TVT, TVT-O, IVS-02 and IVS-04 sets. Results: The highest mean costs (4158 zl) were obtained for the laparoscopic version of the Burch procedure due to the longest time needed for surgical operation, and the most expensive general anaesthesia used as well as disposable tacking device using to staple the mesh to Cooper’s ligament. Mean costs of suburethral slings were comparable, but the TVT-O method was the most expensive (1956.20 zl). Lowest mean costs were noted for the Burch procedure performed as an additional treatment at the end of laparotomy due to uterine or adnexal non-neoplastic diseases. Conclusions: Urinary incontinence surgical treatment in women is associated with substantial costs. In view of the high costs of the laparoscopic version of the Burch procedure and also the lack of long-term results of this operation, we suggest that the procedure should not be a first line of SUI treatment.